Cross-cultural adaptation and validation of the universal Portuguese-version of the Pediatric Functional Assessment of Chronic Illness Therapy - Fatigue (pedsFACIT-F) - Karla P. Fernandes; Bruno S. Teixeira; Benjamin J. Arnold; Tânia M. da S. Mendonça; Sthela M. Oliveira; Carlos Henrique M. da Silva (Elsevier, 2020)
Objective: To cross-culturally adapt and validate the universal Portuguese version of the Pediatric Functional Assessment of Chronic Illness Therapy - Fatigue (pedsFACIT-F). Method: The universal Portuguese version of the pedsFACIT-F was cross-culturally adapted and validated in 323 children and adolescents aged 8-18 years, 173 healthy individuals, and 150 with chronic diseases (cancer, juvenile idiopathic arthritis, and diabetes). Reliability (internal consistency and test-retest reliability) was assessed. Item response theory model assumptions were evaluated using confirmatory and exploratory factor analyses. Items were calibrated using a graded response model. Differential item functioning was assessed regarding age, gender, and clinical condition (healthy vs. chronic diseases). Results: No major cultural adaptations were needed. Internal consistency (Cronbach's alpha = 0.84) and test-retest reliability (intraclass correlation coefficient = 0.92) were good. CFA (CFI = 0.92, TLI = 0.90, RMSEA = 0.097) and CFE analysis confirmed sufficient unidimensionality. The data also fit the GRM and demonstrated good coverage of the fatigue construct (threshold parameters range: −1.42 to 4.56). No items demonstrated significant differential item functioning. Conclusion: The universal Portuguese version of the pedsFACIT-F provides a reliable, precise, and valid measure after being assessed by robust psychometric properties. Stability of the measurement properties of the pedsFACIT-F scale allows its use to assess fatigue in clinical research in Portuguese-speaking children and adolescents. Resumo: Objetivo: Adaptar transculturalmente e validar a versão portuguesa universal da escala Avaliação Funcional Pediátrica de Terapia de Doença Crônica - Fadiga (pedsFACIT-F). Método: A versão traduzida para o português universal e adaptada transculturalmente da escala pedsFACIT-F foi validada em 323 crianças (entre 8 e 18 anos), 173 saudáveis e 150 com doenças crônicas (câncer, artrite idiopática juvenil e diabetes). A confiabilidade foi avaliada pela consistência interna e confiabilidade teste-reteste. Os pressupostos do modelo da teoria da resposta ao item foram avaliados por meio da análise fatorial confirmatória e exploratória. Os itens foram calibrados segundo modelo de resposta gradual. O funcionamento diferencial do item foi examinado com respeito à idade, ao gênero e à condição de saúde (saudáveis versus doenças crônicas). Resultados: A adaptação cultural não apresentou dificuldades substantivas. A confiabilidade da consistência interna (alfa-Cronbach = 0,84) e do teste-reteste (correlação intraclasse = 0,92) foram adequadas. As análises da AFC (CFI = 0,92, TLI = 0,90, RMSEA = 0,097) e AFE confirmaram suficiente unidimensionalidade. O estudo de calibração demostrou bom ajuste do MRG e boa cobertura do construto fadiga (variação dos limiares das categorias de resposta: −1,42 a 4,56). Não foi verificada presença de funcionamento diferencial do item significante. Conclusão: A versão portuguesa universal da escala pedsFACIT-F é uma medida confiável, precisa e válida, verificada após análises de propriedades psicométricas robustas. A estabilidade das propriedades de medida da escala permite seu uso para avaliação de fadiga em estudos clínicos com crianças e adolescentes em países lusófonos.